The Emerging Problems and Possible Solutions of forest Ecosystems of Garhwal Himalayas - Sah, V. K.; Singh, Virendra (Indian Forester, 2002)
The present paper deals with the problems of land use pattern, regeneration potential of major forests, causes of forest degradation, biotic pressures on the existing grazing lands and pastures and the threat imposed by soil erosion and their likely solutions in the forest ecosystems of the Garhwal Himalayas. The land should be allocated according to the land capability classes. The root cause of forest degradation is over-exploitation of forest resources and the encroachment and indiscriminate road and hydroelectric darn construction in the fragile forest ecosystem. The condition of existing grazing lands and pastures is poor due to continuous over-grazing. Introduction of improved grasses and legumes, use of fertilizers and proper grazing management practices need to be adopted. Improvement of these forest ecosystems through afforestation, adoption or-proper soil and water conservation measures and forest management techniques are required to be undertaken.